Cote d'Ivoire : Joint Staff Advisory Note on the Progress Report of the Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This Joint Staff Advisory Note focuses on the progress report (PR) of the Poverty Reduction Strategy Paper (PRSP) for Cote d'Ivoire. The PR notes the difficulty of implementing the PRSP in a period of continued political crisis and civil conflict. It emphasizes that economic performance was affected by various domestic shocks. The PR highlights efforts to strengthen public financial management (PFM) and reform the cocoa sector. It also notes several actions undertaken to build and consolidate peace and strengthen social cohesion in the country.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet